A qualitative study of VHA clinicians' knowledge and perspectives on cannabis for medical purposes. (9th February 2021) - Christensen, Vivian A; Nugent, Shannon M; Ayers, Chelsea K; Morasco, Benjamin J; Kansagara, Devan
Abstract: Background: The legalization of cannabis is expanding across the USA, and its use has increased significantly, including among Veterans. Although the Veterans Health Administration (VHA) abides by the classification of cannabis as a Schedule I substance, it recently recommended that clinicians discuss cannabis with their patients. Little is known about VHA clinicians' perspectives on and knowledge of cannabis. Objective: We sought to better understand clinicians' attitudes, beliefs, knowledge and communication with patients regarding cannabis. Methods: We conducted semi-structured phone interviews with 14 VHA clinicians. Interviews were audio-recorded, transcribed verbatim and analysed using qualitative thematic analysis. Results: VA clinicians described ambivalence towards cannabis for therapeutic purposes and identified several factors that inhibit conversations about cannabis use with their patients including discomfort with the lack of product standardization; lack of research examining the effectiveness and risks of cannabis use; unfamiliarity with pharmacology, formulations, and dosing of cannabis; and uncertainty regarding VHA policy. Clinicians had differing views on cannabis in the context of the opioid crisis. Conclusions: VA clinicians face challenges in navigating the topic of medical cannabis. Educational materials about cannabis products, dose and harms would be helpful to clinicians. Lay Summary: Our research study examines Veterans Health Administration clinicians' attitudes, beliefs, knowledge and communication with patients about cannabis (marijuana) use. We conducted phone interviews with 14 VHA clinicians in order to describe their experiences of talking to their patients about cannabis. Interviews were audio-recorded, transcribed and analysed to identify themes. We describe both common and unique experiences. Our findings suggest that VA clinicians have feelings of uncertainty towards cannabis use for medical purposes and described several reasons that prevent conversations about cannabis use with their patients, including discomfort with the lack of product regulation; lack of research examining the effect cannabis has on the body; unfamiliarity with the different cannabis products that are available; and uncertainty about VHA policy. VA clinicians have diverse views of cannabis in relation to the opioid epidemic.